Early stages in the ontogeny of small B‐cell lymphomas: genetics and microenvironment. (10th April 2017) - Ghia, P.; Nadel, B.; Sander, B.; Stamatopoulos, K.; Stevenson, F. K.
Abstract: In this review, we focus on the mechanisms underlying lymphomagenesis in chronic lymphocytic leukaemia, follicular lymphoma, mantle cell lymphoma and splenic marginal zone lymphoma. The cells of origin of these small B‐cell lymphomas are distinct, as are the characteristic chromosomal lesions and clinical courses. One shared feature is retention of expression of surface immunoglobulin. Analysis of this critical receptor reveals the point of differentiation reached by the cell of origin. Additionally, the sequence patterns of the immunoglobulin‐variable domains can indicate a role for stimulants of the B‐cell receptor before, during and after malignant transformation. The pathways driven via the B‐cell receptor are now being targeted by specific kinase inhibitors with exciting clinical effects. To consider routes to pathogenesis, potentially offering earlier intervention, or to identify causative factors, genetic tools are being used to track pretransformation events and the early phases in lymphomagenesis. These methods are revealing that chromosomal changes are only one of the many steps involved, and that the influence of surrounding cells, probably multiple and variable according to tissue location, is required, both to establish tumours and to maintain growth and survival. Similarly, the influence of the tumour microenvironment may protect malignant cells from eradication by treatment, and the resulting minimal residual disease will eventually give rise to relapse. The common and different features of the four lymphomas will be summarized to show how normal B lymphocytes can be subverted to generate tumours, how these tumours evolve and how their weaknesses can be attacked by targeted therapies. Abstract : Content List ‐ Read more articles from the symposium: Targeted therapy in B‐cell malignancies.